ANALYSIS OF THE SCATTERING FROM CONVENTIONAL X-RAY IN THE RADIOLOGY INSTALLATION OF ZAINAB HOSPITAL - Yoki Rahmat; Riri Melani Gustia; Agus Salim (Medical Imaging and Radiation Protection Research Journal, 2022)
Radiation consists of primary radiation and scattered radiation. Primary radiation is radiation that comes out of the X-ray tube, radiation that comes out of the object and is not in the same direction as the primary beam is called scattering radiation. This scattering radiation will increase the amount of radiation dose received. The closer our bodies to the radiation source, the greater the radiation exposure we receive. Based on the principle of external radiation protection to prevent exposure to radiation we can maintain a safe distance at a safe level and use shielding from radiation sources. This research is a type of descriptive quantitative research with an experimental approach. This research was conducted at RSIA Zainab in June 2021. In this study, an x-ray plane was used as a radiation source, a surveymeter as a scattering radiation detection tool, shielding as a protective device and a meter for distance measurement. Radiation distribution is strongly influenced by distance and the use of shielding, this is in accordance with the inverse square law theory which states that the intensity of light or linear waves emitting from a point source is inversely proportional to the square of the distance from the source or the farther the distance the smaller the radiation exposure, and the use of shielding as a protective barrier at the time of exposure is very effective because x-ray radiation does not penetrate with materials that have a high atomic number such as Pb which is used as a shielding coating.